2021
DOI: 10.1051/shsconf/202110803010
|View full text |Cite
|
Sign up to set email alerts
|

Special features of criminal statistics of criminality in the field of sport

Abstract: The modern state of criminality and its statistical analysis are an integral part of any criminological research including the field of sport. Besides the main factors forming the crime rate, the data of the judicial statistics are also influenced by the so-called minor factors that are beyond the statistics. The objective of the present research is to reveal the factors influencing the formation of indicators of statistics in the field of sport. The research uses the systematic, structural and functional, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Based on the empirical material of investigators and criminologists in the field of crime investigation, problems and trends in the development of administrative prejudice in modern Russia have been identified and it has been concluded that in the Russian law of sport enforcement policy there is no single system of mechanisms for the formation of this institution in practice (Malkov 2011). The author of the study proves the lack of mechanisms for the application of administrative prejudice in the criminal law of sport of the Russian Federation (Bezborodov et al, 2021) .…”
Section: Introductionmentioning
confidence: 90%
“…Based on the empirical material of investigators and criminologists in the field of crime investigation, problems and trends in the development of administrative prejudice in modern Russia have been identified and it has been concluded that in the Russian law of sport enforcement policy there is no single system of mechanisms for the formation of this institution in practice (Malkov 2011). The author of the study proves the lack of mechanisms for the application of administrative prejudice in the criminal law of sport of the Russian Federation (Bezborodov et al, 2021) .…”
Section: Introductionmentioning
confidence: 90%